2023
DOI: 10.3390/ijms24043617
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Selected miRNAs in Normal and Cancer-Associated Fibroblasts and in BxPc3 and MIA PaCa-2 Cell Lines of Pancreatic Ductal Adenocarcinoma

Abstract: Therapy for pancreatic ductal adenocarcinoma remains challenging, and the chances of a complete cure are very limited. As in other types of cancer, the expression and role of miRNAs in controlling the biological properties of this type of tumor have been extensively studied. A better insight into miRNA biology seems critical to refining diagnostics and improving their therapeutic potential. In this study, we focused on the expression of miR-21, -96, -196a, -210, and -217 in normal fibroblasts, cancer-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…29 It has been observed that similar to PDAC tissue, cultured hypoxic CAFs exhibit an altered expression pattern of ncRNA. 30 Specifically, researchers found that hypoxic CAFs have increased expression of miR-21 and miR-210. 30 Previous studies illuminated that CAFs can overexpress specific ncRNAs, such as miR-92 and circEIF3K, which can finally upregulate immune checkpoint proteins, such as PD-L1, in cancer cells and enhance tumor immune evasion.…”
Section: ■ Immune Evasion In Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…29 It has been observed that similar to PDAC tissue, cultured hypoxic CAFs exhibit an altered expression pattern of ncRNA. 30 Specifically, researchers found that hypoxic CAFs have increased expression of miR-21 and miR-210. 30 Previous studies illuminated that CAFs can overexpress specific ncRNAs, such as miR-92 and circEIF3K, which can finally upregulate immune checkpoint proteins, such as PD-L1, in cancer cells and enhance tumor immune evasion.…”
Section: ■ Immune Evasion In Pdacmentioning
confidence: 99%
“…30 Specifically, researchers found that hypoxic CAFs have increased expression of miR-21 and miR-210. 30 Previous studies illuminated that CAFs can overexpress specific ncRNAs, such as miR-92 and circEIF3K, which can finally upregulate immune checkpoint proteins, such as PD-L1, in cancer cells and enhance tumor immune evasion. 31,32 Luciferase assay indicated that miR-92 can target and downregulate the expression of large tumor suppressor kinase 2 (LATS2), thereby attenuating the interaction between yes-associated protein 1 (YAP1) and LATS2 and weakening the inhibitory effect of LATS2 on YAP1-mediated expression of PD-L1.…”
Section: ■ Immune Evasion In Pdacmentioning
confidence: 99%